Meningkatkan Kesadaran Moral Ekologis melalui Aktivitas Harian Mahasiswa Pendidikan Guru Sekolah Dasar - Marianus Teti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explore daily activities that can improve ecological moral awareness among students of the Primary School Teacher Education Study Program (PGSD). Using a descriptive qualitative approach, the study focuses on students' daily behaviors such as waste management, energy conservation, and participation in environmental programs. The results show that consistent small habits can shape strong ecological awareness and impact students' character and pedagogical competence. The development of ecological moral awareness is not only essential for students’ personal identity formation but also forms the foundation for instilling character education in elementary school students.